Strategi Pemasaran Bursa Dhammadipa Arama Kota Batu - Kunatan, Henni; Dhamayanti, Wina; Herman (Jounal Nyanadassana, 2024)
The Dhammadipa Arama Bursa is one of the important facilities at Dhammadipa Arama Monastery, providing a variety of devotional items, Buddhist souvenirs, as well as daily necessities such as snacks and toiletries. Inaugurated on July 17, 2011 by Bhikkhu Dhammavijayo Mahathera, the Bursa plays a vital role in supporting the religious and economic activities of the hermitage. This research aims to analyze the marketing strategies used by the manager of the Dhammadipa Arama Bursa in attracting visitors. The research method used is qualitative with the approach of interview, observation, and literature study. The results showed that the Dhammadipa Arama Bursa implemented various marketing strategies, including product, price, place, and promotion strategies. The product strategy includes the provision of Buddhist goods and daily necessities, with the featured product being Dewi Bulan liniment oil. The pricing strategy involves setting prices based on prices from suppliers with a profit of no more than 10%. Place strategy includes a location close to the main gate, but less visible from the outside. Promotion is limited through social media and brochures during major Buddhist celebrations such as Kathina. These findings indicate the importance of the manager's enthusiasm and persistence (Vīriya Balaṁ) in developing the Dhammadipa Arama Bursa to make it better known and beneficial for visitors and for the Dhammadipa Arama Padepokan.